Psychoemotional state of patients after surgical treatment of thyroid diseases through conventional and minimally invasive approaches - L. I. Mostovaya; E. P. Krivoshchekov; I. V. Pismenniy; B. M. Rakhimov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Objective: to assess the psychoemotional state of patients after surgical treatment of thyroid diseases performed by conventional and minimally invasive approaches.Material and methods. The study was conducted in Samara City Clinical Hospital No. 8. We included 60 patients with benign tumors after thyroidectomy from standard or minimally invasive approach. The psychoemotional state was evaluated using psychological tests.Results. Data analysis confirmed that patients who have undergone thyroidectomy through the upper cervical fold experienced less discomfort associated with a postoperative scar than patients in the first group.Conclusion. Thus, thyroidectomy through the upper cervical fold minimizes negative consequences for the self-esteem and social well-being of female patients.